Cyclic congruent

How many triples of positive integers ( a , b , c ) (a,b,c) satisfy a , b , c > 1 a,b,c>1 and the following?

{ a + b 1 ( m o d c ) b + c 1 ( m o d a ) c + a 1 ( m o d b ) \left\{\begin{matrix}a+b\equiv1\pmod{c}\\b+c\equiv1\pmod{a}\\c+a\equiv1\pmod{b}\end{matrix}\right.

If you think that there are infinitely many such triples, submit -1 as your answer.


The answer is 15.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

WLOG, assume that a b c > 1 a\ge b\ge c>1 .

We have 0 < b + c 1 < 2 a 0<b+c-1<2a and a b + c 1 a\mid b+c-1 , so b + c 1 = a b+c-1=a .

Hence, b ( b + c 1 ) + c 1 b\mid (b+c-1)+c-1 or b 2 c 2 b \mid 2c-2 . Since 0 < 2 c 2 < 2 b 0<2c-2<2b , we get b = 2 c 2 b=2c-2 , and a = 3 c 3 a=3c-3 .

Since c a + b 1 c\mid a+b-1 or c 5 c 6 c\mid 5c-6 , we get c 6 c\mid 6 , implies that c { 2 , 3 , 6 } c\in\{2,3,6\} .

If c = 2 c=2 then a = 3 , b = 2 a=3,b=2 , there are 3 permutations in this case.

If c = 3 c=3 then a = 6 , b = 4 a=6,b=4 , there are 6 permutations in this case.

If c = 6 c=6 then a = 15 , b = 10 a=15,b=10 , there are 6 permutations in this case.

So there are 15 \boxed{15} such triples.

Why b+c-1 <2a ?

Kushal Bose - 4 years, 5 months ago

Log in to reply

We assume that a b c a\ge b\ge c before.

Khang Nguyen Thanh - 4 years, 5 months ago

Umm.. I have a bogus solution and need some clarification as to what is wrong...please help:

We convert each of the given congruences into linear equation as shown:

a + b = c x + 1 a+b=cx+1 , b + c = a y + 1 b+c=ay+1 & b z + 1 = c + a bz+1=c+a . Then, we manipulate this linear system of equations to obtain c x a y = a c cx-ay=a-c , a y b z = b a ay-bz=b-a & c x b z = b c cx-bz=b-c . An obvious solution for ( x , y , z ) (x,y,z) would be ( 1 , 1 , 1 ) (-1,-1,-1) . We then substitute these values into our initial equations and get the result a + b = 1 c a+b=1-c , b + c = 1 a b+c=1-a & c + a = 1 b c+a=1-b . Adding these up gives 3 ( a + b + c ) = 3 3(a+b+c)=3 implying a + b + c = 1 a+b+c=1 . But this cannot be true as ( a , b , c ) > 1 (a,b,c)>1 are positive integers.

Anant Chandrasekar - 4 years, 4 months ago

Log in to reply

a , b , c > 1 a,b,c>1 hence x , y , z > 0 x,y,z>0 .

So, x = y = z = 1 x=y=z=-1 is invalid.

Khang Nguyen Thanh - 4 years, 4 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...